Mercury Exposure and Risk of Cardiovascular Disease in Two U.S. Cohorts - Mozaffarian, Dariush; Shi, Peilin; Morris, J. Steven; Spiegelman, Donna; Grandjean, Philippe; Siscovick, David S; Willett, Walter C; Rimm, Eric B (The New England journal of medicine, 2011)
Stored toenail clippings were used to assess mercury exposure in men and women who had had incident cardiovascular events and in matched controls. Participants with higher mercury exposures did not have a higher risk of cardiovascular events, even after adjustment for fish consumption. Controversy has arisen over the risks and benefits of fish consumption in adults. Fish intake is inversely associated with the risk of coronary heart disease, especially fatal coronary heart disease, and ischemic stroke. 1 Fish are also the major source of exposure to methylmercury. 2 , 3 Chronic, low-level methylmercury exposure appears to cause subtle but measurable neurodevelopmental delay in infants, and it is recommended that women of childbearing age, pregnant or nursing mothers, and infants and young children eat no more than two servings of fish per week and also limit their intake of selected species of fish that are especially high . . .